Effectiveness of Tea Twig Liquid Smoke (Camellia sinensis) as an Antiseptic against Microbes in Vivo and In Vitro - Ayu Rahayu Nurul Ni'am; Aulia Nur Arrsy; Salsabila Zahroh; Feldha Fadhila; Nindya Sekar Mayuri; Alfi Rumidatul (Program Studi Pendidikan Biologi FKIP Unpatti, 2025)
Transmission of microorganisms that cause disease in humans occurs directly or indirectly. Prevention efforts can use antiseptics. The content of liquid smoke compounds in tea twigs has the potential to be an antiseptic. The purpose of this study was to determine the effectiveness of liquid smoke from tea twigs (Camellia sinensis) on microbial growth in vitro using the inhibition test method and in vivo swab test on the palms. In the in vitro test, the most effective results were grade 2 liquid smoke with a concentration of 75% with an inhibition zone diameter of 18.1 mm (E. coli ATCC 25922), 15.6 mm (S. aureus ATCC 25923), 32.3 mm (A. flavus ATCC 9643), 4.3 mm (C. albicans ATCC 10231). The results of the in vivo test showed effectiveness in reducing the number of bacterial colonies by an average of 88.33%, and fungal colonies by an average of 91.52%. From the entire questionnaire data, the parameters of aroma, color, dryness are in the criteria of liking and do not cause side effects on the skin. The results of the study showed that liquid smoke from tea twigs has the potential as an antiseptic.